(untitled) (Scientific journal of the Fergana State University, 2026)
The results of our algological research conducted in the water bodies of the Great Fergana Canal (GFC), Northern Fergana Canal (NFC), and Southern Fergana Canal (SFC), located in the Fergana Valley, showed that during the period from 2009 to 2022, a total of 314 species and varieties of algae were identified, of which 76 were indicator-saprobic algae. These 76 species and varieties belong to 5 divisions, 8 classes, 10 orders, 12 families, and 30 genera, representing 58.02% of the total number (136) of indicator-saprobic species and varieties identified in the Fergana Valley.